A Case Study of Perceptions of Students using ICT as an Educational Tool in Private Secondary School in Famagusta, North Cyprus - Maaitah, Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In this research the perceptions of the students’ in the secondary (Class 8) private school (Doğa College) has been investigated on the uses of ICT tools in learning and teachings contexts. At the beginning of the research, in order to grasp the general perception of students a questionnaire had been given to them. Then for an in depth understanding, semistructured interviews had been carried out randomly. The analysis of the questionnaire had been done with the support of an expertise and the semi-structured interviews had been analysed by using contents analysis by the researcher. In the education field today, the uses of technology to supports all sorts of learning and teachings becoming more and more relevant because for teachers it help them to save time for the preparation of their lessons (time consuming one of the findings in this research) and for students lessons become more colorful (this is one of the findings in this research). Finally the results from this research reflected that ICT tools are effective for learning and teaching. Further suggestions by the researcher has been made at the end of this research. Keywords: students’ perceptions, technology, ICT (information communication technology) tools, private school, teaching-learning

Öz: Bu araştırmanın amacı Güz dönemi (2014-15) 8. sınıf (Orta III) öğrencilerinin Bilgisayar Destekli Öğretimle ilgili görüşlerini araştırmaktır. Araştırmada öğrencilere önce anket uygulaması yapılmıştır ve daha sonrada gönüllük bazında yarı yapılandırılmış mülakat uygulanmıştır. Bu araştırmadan elde edilen verilere göre öğrenciler Bilgisayar Destekli Öğretim Araçlarının derslerde genelde uygulanabileceğini savunmuştur. Günümüzde eğitim sistemine bakılacak olursa, teknoloji kullanımının hem öğrenimde hem de öğretimde çok önemli katkıları vardır. Örnek verecek olursak öğretmenler açısından derslerde zaman tassarufu (araştırma bulgusu), öğrenciler açısından da derslerde çeşitlilik ve motivasyonu artırma (araştırma bulgusu) bulguları verilebilir. Sonuç olarak yapılan bu araştırmada, Bilgisayar Destekli Öğretim Araçlarının derslerde etkili olduğu öğrenci görüşleri tarafından ortaya konulmuştur ve araştırmacı tarafından ise bazı destekleyici önerilerde bu araştırmanın sonunda ortaya konulmuştur. Anahtar Kelimeler: Öğrenci görüşleri, teknoloji, bilgisayar destekli öğretim araçlar, özel okul, öğretme-öğrenme
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Computer Education and Instructional Technologies, 2016. Supervisor: Assist. Prof. Dr. Bengi Sonyel.
Keywords: Computer Education and Instructional Technologies; Information and Communication Technologies in Education Famagusta (Cyprus, North); Education; Computer network resources; Student Perceptions; Educational Technology; E-Learning; Teaching; Students’ perceptions; technology; ICT (information communication technology) tools; private school; teaching-learning